Association of Diet Quality and Breast Cancer Incidence in the Multiethnic Cohort (MEC). (29th May 2020) - Cruz, Rica Dela; Park, Song-Yi; Shvetsov, Yurii; Boushey, Carol; Monroe, Kristine; Marchand, Loïc Le; Maskarinec, Gertraud
Abstract: Objectives: Healthy eating patterns assessed by diet quality indexes (DQIs) have been related to lower risk of cancer incidence and mortality; however, the association between DQIs and breast cancer risk is still unclear. This study investigated the relation of DQIs with breast cancer incidence among diverse women from the Multiethnic Cohort (MEC). Methods: At baseline (1993–1996), 101, 291 female participants of five major racial/ethnic groups (African Americans, Native Hawaiians, Japanese Americans, Latinos and whites) aged 45–75 years completed a survey including a validated food frequency questionnaire. Scores for Healthy Eating Index 2015 (HEI-2015), Alternate Healthy Eating Index 2010 (AHEI-2010), alternate Mediterranean diet score (aMED), and Dietary Approaches to Stop Hypertension (DASH) score were calculated and divided into quintiles (Q1-Q5). Cox regression was applied to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for the association between DQIs and breast cancer risk, with adjustment for known risk factors including body mass index (BMI) among others. Results: During a mean follow-up of 17.4 years, 7769 breast cancer cases were identified through linkage to tumor registries. The respective HRs for Q5 vs. Q1 were: 1.06 (95% CI, 0.98–1.14) for HEI-2015, 0.96 (95% CI, 0.90–1.04) for AHEI-2010, 1.01 (95% CI, 0.94–1.09) for aMED, and 0.95 (95% CI, 0.88–1.02) for DASH. No significant dose-response relations of DQIs with breast cancer risk were observed (all Ptrend ≥ 0.07). HRs analyzed by ethnic group also resulted in null findings with no significant dose-response relations and no significant Q5 vs. Q1 associations of DQIs with breast cancer risk (all Ptrend ≥ 0.14). For example, the respective HRs for the HEI-2015 by race/ethnicity were: 0.96 (95% CI, 0.81–1.14) for African Americans, 1.15 (95% CI, 0.90–1.46) for Native Hawaiians, 1.02 (95% CI, 0.89–1.17) for Japanese, 1.08 (95% CI, 0.88–1.33) for Latinas, and 1.08 (95% CI, 0.92–1.27) for whites. Conclusions: Although adherence to DQIs was not associated with breast cancer risk overall or within racial/ethnic groups, nutrition remains important in breast cancer prevention as obesity, a strong modifiable risk factor, may be influenced by diet quality. Funding Sources: This work was supported by grants from the National Cancer Institute.